COMPARING FORMER ASSUMPTION UNIVERSITY OF THAILAND STUDENTS’ ASPIRATIONS TO ENGLISH PRONUNCIATION MODELS WHILE AT UNIVERSITY LEVEL WITH THEIR EXPOSURE TO ENGLISH PRONUNCIATION MODELS AFTER GRADUATION - Tassev, Valentin Valentinov (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2023)
The overall objective of this study was to examine the relationship between former Assumption University of Thailand (AU) students’ aspirations to English pronunciation models at the university level and in general, their daily exposure to English pronunciation models in a post-university environment, at work, and for socializing purposes after graduation. More precisely, this study tried to compare students’ aspirations to the pronunciation models of native speakers (NSs) of English with the pronunciation models of non-native speakers (NNSs) of English. The study employed the use of a questionnaire, and the data was collected and analyzed solely quantitatively. The study found that from students’ perspectives, the NS English pronunciation models were the preferred models to be learned at the university level and, also, were the desirable models for the purpose of general communication in English. Nevertheless, when examining students’ daily experiences in terms of their communication in English after graduation, the study found that students interacted with NNSs of English more than with NSs and, therefore, were exposed to NNS norms more frequently. As the findings suggest, students might hold a certain bias toward NS norms, and their aspirations, therefore, could be largely socially-constructed. Furthermore, this study implies that Thai learners of English need to be taught and exposed to a large variety of pronunciation models of English, especially in intercultural and international settings where English serves different communicative ends and functions in different forms, such as Thailand.